2019
DOI: 10.1021/acsptsci.9b00020
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment of Erythromycin and Furamidine Provides Additive and Synergistic Rescue of Mis-splicing in Myotonic Dystrophy Type 1 Models

Abstract: Myotonic dystrophy type 1 (DM1) is a multi-systemic disease that presents with clinical symptoms including myotonia, cardiac dysfunction and cognitive impairment. DM1 is caused by a CTG expansion in the 3’ UTR of the DMPK gene. The transcribed expanded CUG repeat RNA sequester the muscleblind-like (MBNL) and up-regulate the CUG-BP Elav-like (CELF) families of RNA-binding proteins leading to global mis-regulation of RNA processing and altered gene expression. Currently, there are no disease-targeting treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…Immunofluorescence Microscopy. The protocol was carried out as described with minor modifications (66). Frozen vastus lateralis (quadriceps) muscle from HSA LR mice was sectioned into 8-μm slices onto slides and fixed with 4% PFA for 15 min at room temperature (RT), permeabilized by using 1:1 methanol:acetone (prechilled) for 5 min at −20°C, and blocked by using Background Sniper for at least 30 min at RT (Biocare Medical).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Immunofluorescence Microscopy. The protocol was carried out as described with minor modifications (66). Frozen vastus lateralis (quadriceps) muscle from HSA LR mice was sectioned into 8-μm slices onto slides and fixed with 4% PFA for 15 min at room temperature (RT), permeabilized by using 1:1 methanol:acetone (prechilled) for 5 min at −20°C, and blocked by using Background Sniper for at least 30 min at RT (Biocare Medical).…”
Section: Methodsmentioning
confidence: 99%
“…Toxicity Analysis in Cell Culture. The protocol was carried out as described with minor modifications (66). For myoblasts, ∼1 × 10 4 myoblasts were plated per well in 96-well plates in SkGM-2 BulletKit growth medium (Lonza).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As proof of concept, a recent study reported that two previously characterized compounds that separately displayed efficacy in DM1 models, furamidine and erythromycin, displayed an even greater rescue of mis-splicing in combination than expected from a mere additive effect [110]. Importantly, this combination treatment yielded lower toxicity and fewer off-target effects than when either drug was administered alone in DM1 patient and mouse models [110]. Hence, if combination treatments are a viable therapeutic strategy for treating DM, there are already many unexplored therapeutic avenues that could potentially hold promise.…”
Section: The Future Direction Of Dm Therapeuticsmentioning
confidence: 99%